2019
DOI: 10.1016/j.tranon.2019.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Spin Labeling for Glioma Grade Discrimination: Correlations with IDH1 Genotype and 1p/19q Status

Abstract: Since accurate grading of gliomas has important clinical value, the aim of this study is to evaluate the diagnostic efficacy of perfusion values derived from arterial spin labeling (ASL) to grade gliomas. In addition, the correlation between perfusion and isocitrate dehydrogenase 1 (IDH1) genotypes and chromosome arms 1p and 19q (1p/19q) status of gliomas was assessed. A total of 52 cases of supratentorial gliomas in adults who received ASL imaging were enrolled in this retrospective study. The cerebral blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 35 publications
2
21
0
1
Order By: Relevance
“…They also concluded that CBF values had excellent diagnostic accuracy for the differentiation between high-grade and lowgrade gliomas owing to cost-effectiveness, lack of adverse events, and high acceptibility (18). Thus, our findings were in agreement with these previous reports (18,20).…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…They also concluded that CBF values had excellent diagnostic accuracy for the differentiation between high-grade and lowgrade gliomas owing to cost-effectiveness, lack of adverse events, and high acceptibility (18). Thus, our findings were in agreement with these previous reports (18,20).…”
Section: Discussionsupporting
confidence: 95%
“…Wang et al studied 52 patients with glioma, divide into two groups: low-grade glioma ( n = 16) and high-grade glioma ( n = 36). Their results showed that maxCBF, rmaxCBF, meanCBF, and rmeanCBF values for the low-grade group were significantly lower than those for the high-grade group ( 20 ). A meta-analysis by Kong et al, including 305 glioma patients, also showed that the ASL perfusion values of the high-grade glioma group, including aCBFmax, aCBFmean, rCBFmax, and rCBFmean, were significantly higher than those of low-grade glioma group.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Zeng et al (2017) [25] revealed a signi cant difference in TBF and nTBF values for these groups of patients, but they did not present ROC-analysis results and thus to evaluate ASL-perfusion effectiveness in differentiating cerebral gliomas grade III and grade IV. Wang et al (2019) did not nd any signi cant difference for TBF and nTBF in these two groups of patients.…”
Section: Discussionmentioning
confidence: 54%
“…Many MR/PET studies correlate with multiple advanced imaging parameters like diffusion-weighted imaging (DWI) and Perfusion weighted imaging (PWI) studies on the grading of gliomas, enabling the prediction of recurrence. It is possible to differentiate recurrence vs. radiation necrosis and the false negative in each modality is known (3)(4)(5)(6). PET also has many tracers, each with its specificity and sensitivity (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%